NILAI-NILAI KEARIFAN LOKAL DALAM POLA PENGASUHAN ANAK MASYARAKAT BANJAR:KAJIAN ETNOLINGUISTIK - Jahdiah Jahdiah (Prasasti: Journal of Linguistics)
Each tribe has a different pattern in terms of parenting. Parenting is a way of educating, nurturing, caring for, and guiding children in the family. The research objective is to describe the patterns and values of local wisdom in the parenting pattern of the Banjar society. This study uses a qualitative method with an ethnolinguistic approach. The subject of this research is the people in Pemantang Hambawang  village, Astambul District, Banjar Regency. Data collection uses direct observation and interviews. The results showed that there are four parenting patterns in the Banjar society: 1) infancy parenting, 2) childhood parenting, 3) young parenting and adult parenting. The parenting pattern in the Banjar people contains the local wisdom such as 1) religious values, 2) educational values, 3) moral values, 4) cooperation values, and 5) educational value.